Freeness of certain torsion-free abelian groups / Ngu Min Hui - Ngui, Min Hu (2012)
One of the old problems in abelian group theory is the following: When is a Torsion-free Abelian Group Free Abelian? This problem has been attacked by many mathematicians. However, until now, we can only have certain criteria under which a torsion-free abelian group is free abelian. A satisfactory answer to this problem has yet to emerge. In this thesis, we will study this problem. We will start with a literature review on the recent development of this problem and present some new results.